Arbitration under international investment agreements : a guide to the key issues - Yannaca-Small, Katia (Oxford University Press, 2010)
Investor-state arbitration is a relatively new dispute settlement mechanism that allows foreign investors the opportunity to seek redress for damages arising out of breaches of investment-related treaty obligations by the governments of host countries. Claims are submitted to independent, international arbitration tribunals, which are called upon to interpret the treaty at hand. Because of the public interest involved in these cases, the awards of these tribunals are subject to much scrutiny and debate. Thus, it has already generated hundreds of cases and created new legal disciplines, inspiri.